A 37-year-old male with extensive cerebral venous thrombosis: Clinicopathological correlation of a rare case - Deepti Mutreja; Rajeev Saxena; T V. S. V. G K. Tilak; Vanmalini Tewari; Nikhil Moorchung; Bhaskar Nandi (Wolters Kluwer Medknow Publications, 2018)
We present the autopsy findings and differential diagnosis of a 37-year-old immunocompetent male patient who presented primarily with extensive cerebral vein thrombosis and was found to have a rare association with JAK2V617F mutation positivity.